2020
DOI: 10.3389/fncel.2020.590034
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles Loaded miRNAs as Potential Modulators Shared Between Glioblastoma, and Parkinson’s and Alzheimer’s Diseases

Abstract: Glioblastoma (GBM) is the deadliest brain tumor. Its poor prognosis is due to cell heterogeneity, invasiveness, and high vascularization that impede an efficient therapeutic approach. In the past few years, several molecular links connecting GBM to neurodegenerative diseases (NDDs) were identified at preclinical and clinical level. In particular, giving the increasing critical role that epigenetic alterations play in both GBM and NDDs, we deeply analyzed the role of miRNAs, small non-coding RNAs acting epigene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 197 publications
(302 reference statements)
0
20
0
Order By: Relevance
“…Downregulation of miRNA-21-5p, miRNA-451a (Gámez-Valero et al, 2019 ), and miRNA-132 and miRNA-212 (Cha et al, 2019 ) was found in exosomes of patients with AD compared with that in patients with DLB and healthy donors. Other works reported the presence of specific miRNAs in EVs from periphery of AD (Cheng et al, 2020 ; Thomas et al, 2020 ). We previously demonstrated a moderate presence of deregulated miRNAs in EVs from patients with PD and AD (Sproviero et al, 2021 ).…”
Section: Discussionmentioning
confidence: 91%
“…Downregulation of miRNA-21-5p, miRNA-451a (Gámez-Valero et al, 2019 ), and miRNA-132 and miRNA-212 (Cha et al, 2019 ) was found in exosomes of patients with AD compared with that in patients with DLB and healthy donors. Other works reported the presence of specific miRNAs in EVs from periphery of AD (Cheng et al, 2020 ; Thomas et al, 2020 ). We previously demonstrated a moderate presence of deregulated miRNAs in EVs from patients with PD and AD (Sproviero et al, 2021 ).…”
Section: Discussionmentioning
confidence: 91%
“…Based on these data, it seems unlikely that the reduction in proliferation induced by C20 SEVs ( Figure 3 B) is related to the increased miR-155-5p therein, given its recognized onco-miRNA properties in the context of glioblastoma. 58 Indeed such properties may be obscured by the simultaneous variation of the other miRNA levels in the same EVs. Noteworthily, oncogenic and onco-suppressive properties have often been reported for miR-146a-5p, 59 so that the actual outcome is difficult to predict.…”
Section: Resultsmentioning
confidence: 99%
“…Another hot topic in AD dilemma is the promising role of lactate level in astrocytes and its possible effect on reinstating cognitive decline of AD. Updated studies spot the role of miRNAs; miR-34a (Sarkar et al, 2016 ), exosomal miR-137 (Thomas et al, 2020 ) and miR-124-3p (Xu S.-Y. et al, 2019 ) in controlling astrocytes lactate shuttle in different brain disorders and the consequent impact of adjusting their levels on cognitive improvement.…”
Section: Discussion and Outlinementioning
confidence: 99%